PENGARUH MEDIA PEMBELAJARAN TANGGA PINTAR TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA PADA MATERI SATUAN PANJANG - ingriani selan (Jurnal PGSD Indonesia, 2025)
This study aims to determine the effect of smart ladder learning media on mathematical problem-solving abilities in the material of length units at Yaswari Soe V Catholic Elementary School. This study used quantitative method with quasi-experimental design, namely Nonequivalent Control Group Design Pretest Posttest, involving one experimental group (using smart ladder media) and one control (without special treatment). The research population were all 83 fourth-grade students, while the sample of this study consisted of 28 fourth-grade students as the experimental group and 27 fourth-grade students as the control group. The research instruments used were test questions and observation sheets. Data analysis in this study used an independent sample t-test. The T-test results showed a t-count value =5.660, which indicated an average difference between the two groups. The significance value (Sig.) obtained was 0.000. Because this value is much smaller than the significance level of 0.05, it can Null Hypothesis (H0) is rejected and the Alternative Hypothesis (H1) is accepted. Based on the results of the comparison of the average values, it was found that there was a difference between the post-test values ​​of the control class and the experimental class of 21.84% so that it can be concluded that there is an influence of the smart ladder learning media on mathematical problem solving abilities because the average post-test value showed a drastic increase in the control class, namely 55.06% and also the experiment, namely 76.9%.